Prognostic value of tumor-infiltrating lymphocytes in patients with early-stage triple-negative breast cancers (TNBC) who did not receive adjuvant chemotherapy. (30th September 2019) - Park, J H; Jonas, S F; Bataillon, G; Criscitiello, C; Salgado, R; Loi, S; Viale, G; Lee, H J; Dieci, M V; Kim, S -B; Vincent-Salomon, A; Curigliano, G; et al.
Abstract: Background: Although stromal tumor-infiltrating lymphocytes (sTILs) have been considered an important prognostic factor in early-stage triple-negative breast cancer (TNBC), there have been limited data on their prognostic value in the absence of adjuvant chemotherapy. Patients and methods: A pooled analysis was carried out using four cohorts of TNBC patients not treated with chemotherapy. sTILs were evaluated in the most representative tumoral block of surgical specimens. Cox proportional hazards regression models were used for invasive disease-free survival (iDFS), distant disease-free survival (D-DFS), and overall survival (OS), fitting sTILs as a continuous variable adjusted for clinicopathologic factors. Results: We analyzed individual data of 476 patients from 4 centers diagnosed between 1989 and 2015. Their median age was 64 years. The median tumor size was 1.6 cm and 83% were node-negative. The median level of sTILs was 10% (Q1−Q3, 4%−30%). Higher grade was associated with higher sTILs ( P  <   10 −3 ). During follow-up, 107 deaths, and 173 and 118 events for iDFS and D-DFS were observed, respectively. In the multivariable analysis, sTILs obtained an independent prognostic value for all end points (likelihood ratio χ 2  = 7.14 for iDFS; P  <   10 −2 ; χ 2   =  9.63 for D-DFS, P  <   10 −2 ; χ 2   =  5.96 for OS, P  =   0.015). Each 10% increment in sTILs corresponded to a hazard ratio of 0.90 [95% confidence interval (CI) 0.82 − 0.97] for iDFS, 0.86 (95% CI 0.77 − 0.95) for D-DFS, and 0.88 (95% CI 0.79 − 0.98) for OS, respectively. In patients with pathological stage I tumors with sTILs ≥30% ( n  = 74), 5-year iDFS was 91% (95% CI 84% to 96%), D-DFS was 97% (95% CI 93% to 100%), and OS was 98% (95% CI 95% to 100%). Conclusion: sTILs add important prognostic information in systemically untreated early-stage TNBC patients. Notably, sTILs can identify a subset of stage I TNBC patients with an excellent prognosis without adjuvant chemotherapy.